Rethinking the Politics of Difference in Indonesia - Thung Ju Lan (Antropologi Indonesia, 2020)
Whilst Indonesia was founded on the principle of Bhinneka Tunggal Ika, the politics of difference has not prevailed as the governing principle in law, society and polity. Instead, domination of the powerful has claimed of assuming the right to govern. During the Suharto’s New Order, the military dictatorship dominated Indonesia for more than three decades with complete impunity whereas in the post‐reformasi era, majority‐minority paradigm seems to rule the country. In both contexts, the rule of law has never been the top priority. Rather, the state of exception, as Carl Schmitt coins, governs and even condones the majority‐minority paradigm. As result the Indonesia’s diversity in ethnicity, religion and class has been subjected to the domination of the majority and its narrative. Papua is one of the cases.